1984
DOI: 10.1227/00006123-198403000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Edema Associated with Meningiomas: Possible Role of a Secretory-Excretory Phenomenon

Abstract: A retrospective study of cerebral edema in 40 patients with intracranial meningiomas seems to demonstrate that the extent of edema is not related to anatomical factors such as location. Histological type is more significant; cerebral edema is usually observed with meningothelial forms. Furthermore, the study of tumor cells by electron microscopic methods indicates that secretory-excretory activity is closely associated with with the production of peritumoral edema. The ultrastructural aspects of this secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
11

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 0 publications
3
43
0
11
Order By: Relevance
“…[13,30] Peritumoral edema originates in the region of the tumor margin and travels by bulk flow through the relatively loosely interconnected fibers of white matter. [16] Peritumoral edema is found in approximately 50% of meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,30] Peritumoral edema originates in the region of the tumor margin and travels by bulk flow through the relatively loosely interconnected fibers of white matter. [16] Peritumoral edema is found in approximately 50% of meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Multiple attempts to correlate the occurrence and degree of peritumoral edema with various factors, including patient gender, tumor location, tumor size, vascularity, cellularity, mitotic activity, steroid receptors, secretory activity, blood supply by intracranial vessels, histological subtype (excepting malignant varieties), and occlusion of veins by the tumor, have failed to establish convincing relationships. [1,3,10,12,13,17,20,[24][25][26]28,30,34] Peritumoral edema has been successfully correlated with the flow cytometric proliferative index in a study of 20 tumors by Crone and coworkers [11] and in a study by Ide, et al, [19] of 57 tumors in which MIB-1 staining was used. Meningiomas with edema contained significantly higher levels of vascular endothelial growth factor messenger RNA than those without edema in 16 tumors analyzed by Kalkanis and associates [22] and in 18 tumors analyzed by Provias and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…23,30 Some authors, however, have reported increased edema in angioblastic and meningothelial meningiomas. 11,23,27,[30][31][32] The most important contributing factor of peritumoral edema is based on the attenuation of the vascular network present in the tumor. 11,23 In our study, calcification was not a dominant feature in RM.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…The pathophysiologic mechanisms at the base of its formation 1,2 are related to ischemia caused by compression of the tumor, 3 stasis followed by venous congestion, 4 and excretory-secretory phenomena. [5][6][7][8] Although the pathogenesis of the edema differs according to whether the tumor is intraaxial or extra-axial, ultrastructural studies have shown that, in both cases, the edema is vasogenic. 9 The advent of functional MR techniques such as diffusion and perfusion imaging and spectroscopy has opened the door to in vivo dynamic and metabolic assessments.…”
mentioning
confidence: 99%